Defect Optimization in Injection Molded Parts Using Metal Epoxy Composite (MEC) as a Hybrid Mold by Taguchi Method - Bin Ismail, Nazirul Ikhwan; Bin Hussin, Radhwan; Bin Illias, Suhaimi (Advanced and Sustainable Technologies (ASET), 2026)
Injection molding with alternative mold materials, such as metal epoxy composite (MEC), offers potential cost reductions and manufacturing flexibility; however, their lower thermal conductivity increases susceptibility to dimensional defects. This study aims to optimize injection molding process parameters to minimize warpage and shrinkage defects in molded parts produced using MEC as a hybrid mold insert. A simulation-based approach was adopted using Autodesk Moldflow, integrated with the Taguchi method for systematic process optimization. Six key process parameters were selected and arranged using an orthogonal array, while signal-to-noise ratio analysis and analysis of variance were applied to identify statistically significant factors. The results indicate that warpage is predominantly influenced by packing pressure and mold temperature, whereas shrinkage is mainly governed by melt temperature. Confirmation tests demonstrated strong agreement between predicted and simulated results, with error margins of 1.12% for warpage and 0.44% for shrinkage, confirming the reliability of the optimization model. Overall, the findings demonstrate that MEC hybrid molds can achieve acceptable dimensional stability when supported by appropriate parameter optimization, thereby providing a cost-effective alternative for small to medium-scale injection molding applications.